Determinan Financial Distress dengan Profitabilitas Sebagai Variabel Moderasi pada Perusahaan Asuransi yang Terdaftar di BEI - Yurika Narulita Maulidya; Dewi Sartika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Financial distress is a stage of decline in the funding situation that occurs before a company is declared bankrupt or experiencing liquidity. Financial difficulties were triggered by experiencing losses in the last few years and being unable to pay off his obligations when they fell due and ultimately experiencing financial distress. In this study, researchers tried to examine the factors that influence financial distress which are moderated by profitability. Research was conducted on insurance companies in Indonesia by conducting analysis using the e-views program so that the influence of each variable on financial statement fraud could be determined. The research results show that only the sales growth factor has no effect on financial distress. As a recommendation, companies are expected to pay more attention to their financial reports, especially those that cause financial distress